How Young Is Too Young? The Evidence of Children Under Five in the English Criminal Justice System. (29th April 2013) - Marchant, Ruth
<x xml:space="preserve">Abstract</x> Perceptions of children's competence as witnesses have shifted repeatedly in the last few decades. Recent international research confirms that very young children can provide reliable descriptions of past events when properly interviewed. In England, the legislative foundations are now in place to enable the evidence of very young children to be heard and tested: clear guidance is available for interviewing teams, prosecutors and advocates, and the judiciary. Yet practice with very young children is erratic across England, both at investigation and at trial. Many practitioners do not feel confident to interview or cross‐examine very young children and in some areas children under five are not interviewed at all. Very few under fives give evidence in English courts, although this is beginning to change. <boxed-text content-type="pullQuote" id="car2273-blk-0001" position="anchor" orientation="portrait"> 'Very few under fives give evidence in English courts, although this is beginning to change' </boxed-text> This paper briefly summarises recent research and current guidance and explores the reasons for variability in practice. A range of practical strategies are suggested to enable very young children to give their best evidence. These strategies link the research base to the author's direct involvement as a registered witness intermediary in more than 70 investigative interviews and criminal trials with children aged two to five.Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Messages Very young children are particularly vulnerable, both to maltreatment and to inept adult questioning. Very young children can give reliable and accurate evidence. There is now consistency and clarity of guidance in relation to the evidence of very young children at interview and at trial. The communicative competence of very young child witnesses depends heavily on the competence of interviewing teams, intermediaries, advocates and the judiciary. <boxed-text content-type="pullQuote" id="car2273-blk-0002" position="anchor" orientation="portrait"> 'Young children are particularly vulnerable, both to maltreatment and to inept adult questioning' </boxed-text>